Formulasi Body Butter Ekstrak Etanol Daun Kelor (Moringa Oliefera L.) Dan Uji Efektivitas Sebagai Pelembab Kulit - Yoan Dasawanti; Ade Rosa Arianti Nasution; Irsa Amalia Tuz Zahara (JURNAL FARMASI DAN MAKANAN, 2025)
Background: Moringa leaves contain secondary metabolites with antioxidant activity that play a role in maintaining skin moisture. Body butter is a cosmetic preparation that is more effective in retaining skin moisture compared to other topical formulations. Objective: To determine the effectiveness of body butter containing Moringa oleifera L. leaf extract in improving skin moisture. Methods: This study was an experimental research. Moringa leaf extraction was carried out using the maceration method. The extract was formulated into body butter at concentrations of 5% (FI), 7% (FII), and 9% (FIII), while the base formulation without extract (F0) served as a negative control. The prepared formulations were evaluated for physical properties, including organoleptic characteristics, homogeneity, pH, viscosity, formulation stability, and skin irritation. The moisturizing effectiveness was measured using a skin analyzer. Results: The results showed that all body butter formulations containing moringa leaf extract were physically stable and did not cause skin irritation. The moisturizing test demonstrated a significant increase in skin moisture at all extract concentrations. The 9% extract formulation (FIII) showed the highest increase in skin moisture, from 18.33% to 57.33% after four weeks, approaching the effectiveness of the positive control (59%). These findings indicate that the moisturizing effectiveness increased with higher extract concentrations. Conclusion: Ethanolic extract of Moringa oleifera L. leaves can be formulated into a stable body butter preparation and is effective as a skin moisturizer. Keywords: Moringa oleifera leaves, body butter, moisturizer, skin analyzer